"Ring up for an appointment": Empirical & oral evidence of commercial & other freedoms in the heyday of the City. (April 2023) - Lai, Lawrence Wai Chung; Davies, Stephen Nicholas Guy; Lau, Prudence Leung Kwok; Leung, Nixon Tit Hei; Chan, Vincent Nok Hang; Chua, Mark Hansley Yang
Abstract: Informed by economic concepts of product competition, this paper uses publicly available and accurate business information on establishment names and addresses obtained from the Yellow Pages of the contemporary Hong Kong telephone book and census socio-economic data backed by oral testimonies, to dispel the myth that the "Kowloon Walled City" was an incarcerated ghetto. The use of this imagery in the title for this City as a built up, politically sensitive zone levelled to the ground to make way for a public Chinese garden shortly before Hong Kong was returned to China, is treated as a form of 'product differentiation' in the academic research marketplace. As a contribution to planning theory, the paper uses the City as a show case of how academic branding, through descriptors, creates images of places and offers a countervailing image. Technically, it demonstrates the immense archival value of telephone directories and business chronicles apart from census data as sources of socially significant data for urban studies and informed re-interpretation of subjective imageries of an urban place. Highlights: Challenge dark views of Kowloon Walled City with socio-economic statistics & oral testimonies Refute representation of Kowloon Walled City as a dark prison Project a bright picture of Kowloon Walled City